HUBUNGAN EFIKASI DIRI DENGAN TINGKAT ANSIETAS MAHASISWA PRAKTIK PROFESI NERS PROGRAM STUDI ILMU KEPERAWATAN FK UNSRAT MANADO PADA MASA PANDEMI COVID-19 - Michelle Franciska Trivena Sanger; Hendro Joli Bidjuni; Andi Buanasari (Universitas Sam Ratulangi, 2022)
Background: During the Covid-19 pandemic nursing students experienced anxiety during clinical learning. The existence of high self-efficacy can manage and control themselves when students experience difficult situations, so that they can push their feelings of stress such as anxiety. The aim of the study is to find out the relationship of self-efficacy with the level of anxiety of students practicing the nursing profession of Manado during the COVID-19 pandemic. The method used in this research is quantitative correlation with a cross sectional study approach and used the General Self Efficacy Scale and Hamilton Anxiety Rating Scale questionnaires. The sample of this research consists of 44 samples using total sampling as a sampling techniques. The data analysis was used using frequency distribution and bivariate analysis using spearman’s test. The results with a significant value 0.000 or smaller than the significant value 0.05 (0.00 < 0.05), so that there is a relationship between self-efficacy and the level of anxiety of the Manado Nurses Professional Practice students during the COVID-19 pandemic. The conclusion high self-efficacy can reduce the risk of anxiety in nursing professional practice students in hospitals during the Covid-19 pandemic, so that it is hoped that it will have an impact on efforts to improve health services in terms of providing nursing care by nursing professional practice students to further improve self-efficacy so that the risk of experiencing anxiety is reduced and can carry out nursing professional practice more optimally during the Covid-19 pandemic.